Acculturation, Education, and Gender Roles: Evidence from Canada - Anke Kessler; Kevin Milligan (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
This paper studies the influence of cultural norms on economic outcomes. We combine detailed information on second-generation female immigrants with historical data from their ancestral source country to see how the cultural endowment received from their fathers affects current decisions. Our results show that education plays a critical role in cultural transmission: lower-educated women exhibit a strong influence of cultural variables while higher-educated women show no influence at all.
Keywords: J16; J22; J61; 330